2015
DOI: 10.1089/bio.2015.0009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in Vivo Ischemic Time on RNA Quality—Experiences from a Colon Cancer Biobank

Abstract: Considerable effort has been made to improve differentiated diagnostics as well as personalized treatment for colorectal cancer patients. High-quality fresh frozen tissue is often required to investigate relevant molecular signatures in these patients. In RNA expression studies, the "RNA integrity number" is widely accepted as a reliable marker of RNA quality. Here, we investigate the feasibility of obtaining high-quality tissue from a colon cancer biobank and the impact of in vivo ischemic time and various te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…All pre-analytical parameters included in this range could alter the integrity of biomolecules contained in tissues and thus also introduce a bias in the results obtained. For example, it has been demonstrated that ischemia time (IT), both warm and cold, as one of the most influencing factors on RNA integrity [9][10][11] . However, no consensus has yet been reached to determine the exact moment in which RNA quality and integrity begin to decrease.…”
mentioning
confidence: 99%
“…All pre-analytical parameters included in this range could alter the integrity of biomolecules contained in tissues and thus also introduce a bias in the results obtained. For example, it has been demonstrated that ischemia time (IT), both warm and cold, as one of the most influencing factors on RNA integrity [9][10][11] . However, no consensus has yet been reached to determine the exact moment in which RNA quality and integrity begin to decrease.…”
mentioning
confidence: 99%
“…The patient material in the clinical data was compiled from the cancer Biobank at the University of Copenhagen [ 37 ]. The clinical data were collected between September 2006 and May 2012 from Roskilde University Hospital [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…an agilent 2100 Bioanalyzer and an agilent rna 6000 nano kit (agilent Technologies, inc.) were used to determine rna quality, according to the manufacturers' protocol. rna integrity numbers (rins) were calculated using agilent Technologies 2100 Bioanalyzer expert software (version B.02.0x; agilent Technologies, inc.), and were presented as a value (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) to indicate the degree of degradation.…”
Section: Procurement Of Tissues a Total Of 18 Carcinoma Tissue Speci-mentioning
confidence: 99%
“…Pre-analytical variables are divided into the pre-acquisition and post-acquisition phases. In the pre-acquisition phase, factors such as anesthesia ( 7 ), surgical trauma ( 8 , 9 ) and in vivo ischemia ( 10 ) might affect the cell integrity and gene expression profiles of the biospecimen, but they cannot be controlled very well because of the uncertainty of clinical treat requirements ( 11 ). Rather, factors such as ex vivo ischemia time, delayed processing time and processing temperature, which are crucial for bio-specimen quality ( 12 ), can be controlled and standardized effectively.…”
Section: Introductionmentioning
confidence: 99%